Agreement between serological data on schoolchildren and the number of malaria cases in the remaining high-burden villages of Indonesia - Kosasih, Ayleen; Utami, Retno Ayu Setya; Noviyanti, Rintis; Elyazar, Iqbal R. F.; Lestari, Karina Dian; Raimanus, Valentinus Seran; Longley, Rhea J.; Baird, J. Kevin; Robinson, Leanne J.; Sutanto, Inge; Mueller, Ivo (Frontiers in Malaria, 2024)
Introduction: In areas where malaria transmission has been successfully reduced, surveillance based solely on clinical cases becomes increasingly challenging. Antibodies generated by the host in response to malaria infections may persist in the circulation for several months or longer. We assessed a serological surveillance tool to measure malaria transmission in eastern Indonesia where reported cases have been recently declining. Methods: In June 2021, we conducted a cross-sectional survey of elementary schoolchildren aged 5 to 14 years residing in six villages in an endemic area of West Timor, Indonesia. Annual Parasite Incidence (API, cases/1000 residents/year) of these villages ranged from 0.0 to 4.1 in 2021. Finger-prick plasma samples were tested using a multiplexed Luminex MAGPIX® bead array system to measure IgG antibodies against a panel of 8 Plasmodium vivax antigens. Using a random forest classification algorithm, individuals with predicted exposure to P. vivax in the prior 9-months were identified. Results: 15 of 398 (4%) schoolchildren were seropositive for recent P. vivax exposure. Remarkably, 87% (13/15) of seropositive children were from one village, the one with the highest API (4.1). In contrast, one seropositive child was from a village with an API of 1.3, and another from a village with an API of 0.0. Conclusion: Our serological survey data confirms the reported malaria cases from PHC in the villages with likely ongoing transmission. Malaria programs may consider Lamea as the target for intervention.